UPAYA PENANGANAN LOKASI RAWAN KECELAKAAN RUAS JEMBATAN CIKUNDUL JALAN RAYA PUNCAK JAWA BARAT - Prasetyanto Sudiatmono, Dwi; Santosa, Wimpy (Jurnal Transportasi, 2010)
Traffic safety on the highway is a complex problem involving the behavior of drivers, driving conditions, vehicle characteristics, and features of the highway. Traffic accidents can be reduced with safety programs, in an attempt to address these traffic accident problems. This study aims to reduce the severity and frequency of road accidents. An observation made in Cikundul Bridge, located at Puncak Road, West Java. This location is a dangerous location, which needs to be given priority for remedial based on analysis of existing traffic accident data. The remedial that needs to be done includes installation of better traffic signs, installation of road markings, installation of fences, improving road geometric conditions, and improved visibility.Keywords: traffic safety, accident severity, road safety program